Effect of underlying boron nitride thickness on photocurrent response in molybdenum disulfide - boron nitride heterostructures. Issue 7 (6th January 2016) - Wasala, Milinda; Zhang, Jie; Ghosh, Sujoy; Muchharla, Baleeswaraiah; Malecek, Rachel; Mazumdar, Dipanjan; Samassekou, Hassana; Gaither-Ganim, Moses; Morrison, Andrew; Lopez, Nestor-Perera; Carozo, Victor; Lin, Zhong; et al.
Abstract: Abstract : Here we report on the photocurrent response of two-dimensional (2D) heterostructures of sputtered MoS2 on boron nitride (BN) deposited on (001)-oriented Si substrates. The steady state photocurrent ( I ph ) measurements used a continuous laser of λ = 658 nm ( E = 1.88 eV) over a broad range of laser intensities, P (∼1 μW < P < 10 μW), and indicate that I ph obtained from MoS2 layers with the 80 nm BN under layer was ∼4 times higher than that obtained from MoS2 layers with the 30 nm BN under layer. We also found super linear dependence of I ph on P ( I ph ∝ P γ, with γ > 1) in both the samples. The responsivities obtained over the range of laser intensity studied were in the order of mA/W (∼12 and ∼2.7 mA/W with 80 nm BN and 30 nm BN under layers, respectively). These investigations provide crucial insight into the optical activity of MoS2 on BN, which could be useful for developing a variety of optoelectronic applications with MoS2 or other 2D transition metal dichalcogenide heterostructures.